Virtual reality in emotion regulation: A scoping review - Macey Anna-Leena; Macey Joseph; Hamari Juho (Germany, 2022)
Academic research investigating virtual reality (VR) is growing rapidly; as a result of VR becoming more easily accessible, it has become a more viable tool for helping individuals regulate their emotions. This research aims to provide an overview of the field and the contexts in which VR has been implemented to facilitate emotion regulation. Results indicate that although VR has been used to facilitate ER for over two decades, empirical research in the field has remained somewhat static until 2018. Furthermore, the contexts in which it has been employed have remained narrow with more than half of all included publications utilising VR to administer exposure therapy. While the recent increase of published works in the field, combined with more varied uses of VR, indicate a broadening of the field this work highlights several gaps in the extant literature, identifying a series of potential avenues for future research.
Proceedings of the 6th International GamiFIN Conference Tampere, Finland, April 26-29, 2022 (Organized as an online conference).